A Presumably New Arbovirus 'Tulenity' (seal) Isolated from Ixodes Putus Ticks Collected at a Seashore Bird Colony in the Okhotsk Sea - Lvov,D. A.; Timoffeeva,A. A.; Chervonsky,V. I.; Gromachevsky,V. L.; Klisenko,G. A. (1974)
A study has been made of three strains (LEIV-4C, LEIV-6C, LEIV-62C) of a presumably new arbovirus named 'Seal', which has been isolated in 1969 from Ixodes (Ceratixodes) putus ticks collected in the seashore bird colony (Uria Aalge) on the Tuylen' island of the Okhotsk sea. According to filtration data, the size of virus is less than 50 microns. The virus, containing RNA, is sensitive to the action of ether and sodium deoxicholate; it causes the death of suckling mice and three week old mice by infection (intracerebral). In rabbits, it produces the formation of HA and CF antibodies, and agglutinates goose erythocytes at the optimal pH of 6. Trans. of unidentified Russian language mono. pub. by Ivanovsk Institut of Virusology of the Academy of Medical Sciences of the USSR, Moscow, 14 Apr 70.